Hardcore education: The case of Sexual Freedom in Denmark. Issue 2 (1st June 2015) - Schaefer, Eric
This article addresses John Lamb's Sexual Freedom in Denmark (Von Hellen, 1970), an American film that explored the liberalization of censorship in Denmark in the late 1960s while advocating for similar changes in the United States. Lamb used explicit sexual imagery with educational material to promote enlightened attitudes. The film was a box office success and became a popular tool with teachers while paving the way for hardcore movies on American screens.